2023
DOI: 10.3390/healthcare11081104
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effectiveness of a Novel Intervention Integrating Physical Therapy Exercise and Dance Movement Therapy on Fall Risk in Community-Dwelling Older Women: A Randomized Pilot Study

Abstract: This pilot study presents a novel fall prevention intervention that integrates physical therapy exercise (PTE) and dance movement therapy (DMT) to address both physical and emotional fall risk factors, as well as factors influencing adherence to treatment. The aim of this study was to examine the feasibility and effectiveness of the intervention in a sample of eight older women (median = 86 [81.25–90.75] years) from a day center for senior citizens. The intervention, based on the Otago Exercise Program and DMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 110 publications
1
3
0
Order By: Relevance
“…The findings of that study demonstrated that engaging in dance activities involving movement mirroring, spontaneous expression, and creativity elicited a sense of surprise among the grandmothers as they discovered newfound abilities in their bodies, such as strength and power, despite experiencing movement difficulties. In addition, the current finding is also consistent with the results of our previous study, which indicated a trend towards improvement in the physical components of self-perceived health status in the PTE + DMT group, but not in the PTE group ( Pitluk Barash et al, 2023 ).…”
Section: Discussionsupporting
confidence: 93%
“…The findings of that study demonstrated that engaging in dance activities involving movement mirroring, spontaneous expression, and creativity elicited a sense of surprise among the grandmothers as they discovered newfound abilities in their bodies, such as strength and power, despite experiencing movement difficulties. In addition, the current finding is also consistent with the results of our previous study, which indicated a trend towards improvement in the physical components of self-perceived health status in the PTE + DMT group, but not in the PTE group ( Pitluk Barash et al, 2023 ).…”
Section: Discussionsupporting
confidence: 93%
“…Dance classes using the RIPE Dance approach have the potential to be scaled for greater access in the community and in aged care. A pilot randomised study testing a model similar to RIPE Dance which integrates physical therapy exercises for fall prevention with dance movement therapy has demonstrated the program’s feasibility and potential benefits ( 136 ). Dance classes require little equipment and are not resource intensive to organize, however they do require an excellent and committed teacher with technical, creative and interpersonal skills and a caring, outgoing personality ( 96 , 112 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of aerobic exercise on mental well-being and physical fitness have been extensively demonstrated [9,10]. Several studies have revealed the relationship between fitness and cognition in different populations [11].…”
Section: Exercise and Cognitionmentioning
confidence: 99%
“…Several neurocognitive functions are modulated during the menstrual cycle, pregnancy, and throughout a woman's entire lifespan. Reproductive hormones are involved in the function of the hippocampus and prefrontal cortex, as well as cognitive performance, including verbal, memory, and executive functions [7][8][9][10]. The general pattern of age-related preservation and decline indicates that prefrontal white matter is the most susceptible to the influence of age [2,3,8].…”
Section: Introduction 1cognitive Function In Perimenopausal Womenmentioning
confidence: 99%